The gender of justice system: Women's access to justice in Turkey. (December 2016) - Hatıpoğlu-Aydın, Duygu; Aydın, Mustafa Berkay
Abstract: Access to justice as a practical and process based concept may be defined as the capacity of people to access judicial institutions which shall bring solution to common judicial problems of the people. While the burdens before access to justice are common for various groups, women may suffer more frequently accessing these institutions and have difficult time to overcome the burdens due to other structures which produce inequality. The article focuses on women's access conditions to justice in Turkey and these conditions are assessed from the perspective of deficiency of normative frame and sufficient legal mechanisms which protect women's rights, information deficiency regarding their rights, advice and representation deficiency in their legal problems, burdens before women's access to judicial institutions, high proceeding costs, along with the slow pace to hear actions, complex procedures and corruption in the system, vagueness of legal language, and inability to execute court decisions topics.